Platelet-rich plasma stimulates cytokine expression and alkaline phosphatase activity in osteoblast-derived osteosarcoma cells - Herrera, Bruno S. [UNESP]; Coimbra, Leila S. [UNESP]; Bastos, Alliny S. [UNESP]; Teixeira, Simone A.; Steffens, Joao P. [UNESP]; Muscara, Marcelo N.; Spolidório, Luis Carlos [UNESP] (Pergamon-Elsevier B.V. Ltd, 2012)
Objective: The aim of this study was to investigate the effects of PRP on SAOS-2 cells in terms of cytokine expression, cell activity and oxidative stress.Design: Cell line SAOS-2 (1 x 10(5) cells/mL) were grown in culture medium alpha-MEM with 10% FBS for 24 h and stimulated (or not) with PRP at concentrations of 3, 10 and 20%, LPS (E. coli, 10 g/mL) and IL-1 beta (1 mg/mL) for 24 h. The supernatant was collected and analyzed for the expression of cytokines in a panel array, ALP using a commercial kit and NO2- with Griess reaction method. Also, the cells were analyzed using Western blot for RANKL and slot blotting for nitrotyrosine expression.Result: There were no significant differences amongst the groups in terms of NO2-, protein nitrotyrosine content and RANKL expression. However, all stimuli increased ALP activity and in case of PRP, it was in a dose-dependent manner (p < 0.001). Also, all stimuli induced an increase in cytokines and chemokines expression, but only PRP promoted an increase of component C5, sICAM-1 and RANTES expression. Whilst IL-1 receptor antagonist (IL-1ra) expression was down-regulated by PRP, both LPS and IL-1 beta caused up-regulation of this cytokine.Conclusions: PRP can stimulate osteoblast activity and cytokine/chemokine release, as well as indicate some of the mediators that can (and cannot) be involved in this activation. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Osteoblast(s); Periodontal regeneration; Reactive oxygen species (ROS); Cell biology